Agricultural Cooperation and its Role in Rural Social Life (1921-1929) - Mahmudkhan Mahmudov (Researchparks Publishing, 2023)
This article discusses agricultural cooperation and its role in rural social life in Uzbekistan in 1921-1929 during the period of new economic policy. In the article, the author analyzed the historical conditions of that time, specific aspects of rural social life.